Abordagem bourdiseana do campo e do capital científico da pesquisa em contabilidade ambiental no Brasil - Rodrigues, Raquel da Silva (2020)
In this review, one sought to analyse the constitution of the scientific field of the Brazilian environmental accounting from the concepts of Pierre Bourdieu. This is a positivist study, with a quantitative and exploratory approach, and bibliometric and documentary procedures for measuring pure and institutional scientific capital, whose information was collected in the database of the Lattes Platform of the National Council for Scientific and Technological Development (CNPq) in order to identify the research agents. The results showed a total of 137 research-agents characterized in accordance with the demographic and academic profile – expressed by qualification, professional experience, intellectual production, positions held and participation in boards, councils, commissions and consultancies – that might be analysed in three categories: agents, scientific capital and scientific field. It was confirmed that the Brazilian scientific field of environmental accounting includes research agents distributed in all regions of Brazil with a slight predominance of female agents. It was also found that the research agents are more dedicated to research than to administrative positions, that is, the structure of the scientific field is greater due to the pure scientific capital. Regarding the dynamic of the field, the presence of new researchers and an increase in the number of scientific research publications over the years are noted.